Role of portable chest radiography in management of COVID-19: Experience of 422 patients from a tertiary care center in India - Goyal, Alka; Tiwari, Raghav; Bagarhatta, Meenu; Ashwini, B; Rathi, Bhavyansh; Bhandari, Sudhir (Indian Journal of Radiology and Imaging, 2021)
Objective: To analyze radiological changes in portable chest radiographs in coronavirus disease-19(COVID-19) patients to optimize the management of hospitalized patients. Methods: We retrospectively reviewed 638 portable radiographs of 422 hospitalized COVID-19 patients with RT-PCR confirmed COVID-19 infection. All the radiographs were reported in a structured format by two experienced radiologists. A severity score was assigned to every Chest Xray (CXR) and correlation was done with the CT scans whenever available. Results: Out of 422 baseline portable radiographs assessed,the ratio of male: female patients was 337:85 that is 79.8% were males and 20.14% were females.The mean age was 50.5 years and the range was 17–84 years.Of these 422 patients, 187 patients (44.3%) had abnormal baseline CXR. 161 out of 187 (86%) had either typical or indeterminate findings for COVID-19 pneumonia, rest 26 (13.9%) patients had CXR findings not consistent with COVID-19, like pleural effusion, hydropneumothorax, or lung cavity.Most commonly observed CXR findings in COVID 19 pneumonia were bilateral, multifocal air space opacities (consolidation and ground-glass opacities) predominantly involving lower zones and peripheral lung fields. X-ray identifiable lung changes of COVID-19 were mostly seen at 9-11 days after symptom onset. Conclusion: The presence of multifocal air-space opacities with bilateral, peripheral distribution on chest radiograph is highly suggestive of COVID-19 pneumonia in this pandemic setting.Portable chest radiography is a widely available and quicktool for estimating the evolution and assessing the severity of lung involvement of COVID-19 pneumonia in hospitalized symptomatic patients.
Keywords: CT-computed tomography; CXR-chest radiography; GGO-ground glass opacity; RT-PCR – reverse transcriptase polymerase chain reaction